2022
DOI: 10.3389/fnut.2022.892426
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Dipeptidyl Peptidase-4 by Flavonoids: Structure–Activity Relationship, Kinetics and Interaction Mechanism

Abstract: With the aim to establish a structure-inhibitory activity relationship of flavonoids against dipeptidyl peptidase-4 (DPP-4) and elucidate the interaction mechanisms between them, a pannel of 70 structurally diverse flavonoids was used to evaluate their inhibitory activities against DPP-4, among which myricetin, hyperoside, narcissoside, cyanidin 3-O-glucoside, and isoliquiritigenin showed higher inhibitory activities in a concentration-dependent manner. Structure-activity relationship analysis revealed that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…Representative DPP-IV inhibitory avonoids (1-72) and other aromatic compounds (73-100) are summarized in Table 1. Perhaps, one of the most extensive analyses of the effect of avonoids on DPP-IV was carried out by Pan et al, 44 who analyzed 70 different avonoids of different structural groups using a human recombinant enzyme and monitoring the reaction by measuring the uorescence generated by the substrate Gly-Pro-7-amido-4-methyl coumarin hydrobromide.…”
Section: Natural Products With Dpp-iv Inhibitory Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Representative DPP-IV inhibitory avonoids (1-72) and other aromatic compounds (73-100) are summarized in Table 1. Perhaps, one of the most extensive analyses of the effect of avonoids on DPP-IV was carried out by Pan et al, 44 who analyzed 70 different avonoids of different structural groups using a human recombinant enzyme and monitoring the reaction by measuring the uorescence generated by the substrate Gly-Pro-7-amido-4-methyl coumarin hydrobromide.…”
Section: Natural Products With Dpp-iv Inhibitory Propertiesmentioning
confidence: 99%
“…They also demonstrated that the uorometric method is more sensitive than the colorimetric. 39,72 Regrettably, unlike Proença et al, 39 Pan et al, 44 did not include the results for any positive control in the study; therefore, potency comparisons between such control and the tested avonoids cannot be performed. In the study conducted by the former authors, natural avonoids did not reach 50% inhibition at 200 mM and were thus less effective and potent than positive controls assayed (sitagliptin and diprotin A with IC 50 values of 0.064 and 31 mM, respectively).…”
Section: Natural Products With Dpp-iv Inhibitory Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…These residues are within a 10 Å radius from the catalytic triad and could play a relevant role in controlling the noncovalent binding and catalytic properties of DPP4 due to differential electrostatic effects arising from their possible protonation forms (Figure A). , His126 is part of the S2 recognition domain of DPP4 and has been proposed to play a structuring role by engaging in hydrogen bonding interactions with the substrate anchoring residue Glu205 (Figure B) . His126 has also been proposed as a binding site residue for noncovalent DPP4 inhibitors. Asp663 also belongs to the S2 recognition subsite and is responsible for the differential substrate specificity and enzyme activity between DPP4 and the homologous fibroblast activation protein α (FAP) . This residue locates nearby the anionic side chain of Glu206 and could form a hydrogen bond that has been associated with the appearance of downfield resonance signals at ∼16 ppm in native and mutant forms of DPP4 in ligand-free and complex states with covalent and noncovalent inhibitors (Figure C) .…”
Section: Introductionmentioning
confidence: 99%